The era of virtual reality in medical education: do we still need the dissection table? - Sarma, Vivek Parameswara (International Surgery Journal, 2021)
For the benefit of the uninitiated, the MBBS course begins with the three basic subjects, anatomy, physiology and biochemistry. Of these, the most intensive and gruelling for most is the subject of anatomy. And within the said subject, the most demanding is the human dissection table. It can even be considered as the ultimate icon of initiation into medical education. It has tragedy, dark comedy and drama in different measures. The image of young students huddled around a shrivelled human body, usually referred to medically as a ‘Cadaver, on a non-descript table, ever endures in mind of all doctors, for better or worse. This happens in a hall ever filled by the suffocating smell of formalin and the dread of the watchful eye of demonstrators trained like hounds. The course in anatomy is split into different sections on limbs, thorax, abdomen, head and neck etc, with corresponding dissection studies to be made on the cadaver, which shall henceforth be referred to as the ’body’.